The Governance of the Arctic Environment: The EU and US Contribution - VIGNI, PATRIZIA (European University Institute, 2013)
The Arctic, as a unique area of our planet, has always attracted the interest of humanity. Despite its uniqueness, the Arctic is more difficult to preserve than other areas of our planet. The presence of ice makes this region particularly fragile and exposed to environmental degradation. The environmental threats that have recently increased their impact on the Arctic are: first, resource exploitation; second, shipping and tourist activities; and finally, climate change. Special protection seems to be required for the Arctic. The establishment of an effective international regime (like the Antarctic Treaty System) for the management of the Arctic should be a common aim of both the EU and US. However, regardless of the existence of a global regime for the Arctic, the EU and US may so far exercise their authority in an “environmentally responsible manner” in order to ensure the protection of the Arctic as a “common good” that must be managed in the interest of humankind.